Impact of Body Composition on Prognosis and Dose-Limiting Toxicities on Metastatic Colorectal Cancer - da Silva Dias, David; Machado, Mafalda; Trabulo, Carolina; Gosálbez, Beatriz; Ravasco, Paula (Frontiers in Nutrition, 2022)
Sarcopenia is a progressive skeletal muscle disease, often present in oncological patients, that is associated with multiple adverse events such as worse prognosis, physical performance and quality of life. Body composition evaluation by computed tomography (CT) cross-section at L3 vertebrae region appears to be a precise method to quantify skeletal muscle. Optimal cut-offs for the definition of sarcopenia are not yet established, therefore the incidence of sarcopenia varies according to different studies. The main goal was to evaluate the presence of sarcopenia in metastatic colorectal cancer (mCRC) patients and its impact on overall survival (OS) and dose limiting toxicities (DLT). A retrospective cohort study of 178 patients with mCRC under first line chemotherapy (ChT) in association with target therapy, in two hospital units, between January 2015 and December 2018. Skeletal mass area (SMA) was quantified with NIH ImageJ software in CT cross-sectional images at the L3 vertebrae region. Statistical analysis was performed with IBM SPSS v25 software. Median age was 62 (SD ± 11) years old, 65% were male and 62.9% had ECOG performance status of 0. The cut-off value was established based on ROC analysis, with sarcopenia defined as SMI < 49.12 cm2/m2 for men and < 35.85 cm2/m2 for woman. Despite the mean body mass index (BMI) of 25.71 (± 4.71) kg/m2, half of the patients presented sarcopenia. In a multivariate analysis using a Cox regression model, an association was observed between OS and higher ECOG PS (p=0.014; HR 5.46, CI 95% [1.42-21.10]), neutrophil-to-lymphocyte ratio (NLR) >2.80 (p=0,038; HR 2.20, CI 95% [1,05-4.62]) and sarcopenia (p=0.01; HR 4.73, CI 95% [1.85-12.09]). Additionally, in a logistic regression model, age (p=0.014; OR 1.09, IC 95% [1.02-1.16]) and sarcopenia (p=0.030, OR 4.13, IC 95% [1.15-14.8]) were associated with higher incidence of DLT. CT evaluation of body composition at the L3 region allows for the quantification of sarcopenia, providing prognostic information and predictive value of DLT in mCRC patients, although the establishment of optimal cut-off values are required for implementation in clinical practice. A multimodal strategy to delay muscle waste should be considered in these patients.